Framing Effects in Younger and Older Adults - Kim, Sunghan (2005)
A growing literature on decision making in older adults suggests that they are more likely to use heuristic processing than are younger adults. We assessed this tendency in the context of a framing effect, a decision-making phenomenon whereby the language used to describe options greatly influences the decision maker’s choice. We compared decision making under a standard (“heuristic”) condition and also under a “justification” condition known to reduce reliance on heuristics. In the standard condition, older adults were more susceptible than younger adults to framing but the two groups did not differ when participants were asked to provide a justification. Thus, although older adults may spontaneously rely more on heuristic processing than younger adults, they can be induced to take a more systematic approach to decision making.